2006
DOI: 10.1007/s11136-005-4181-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fatigue in Parkinson’s Disease: The Fatigue Impact Scale for Daily Use (D-FIS)

Abstract: The Fatigue Impact Scale for Daily Use (D-FIS) was used in a cross-sectional study including 142 consecutive Parkinson's disease (PD) patients. Usual clinical measures for PD, the Montgomery-Asberg Depression Rating Scale and the Parkinson's Disease Questionnaire-8 items were applied. In addition to the D-FIS, patients with fatigue (67.6%, PWF) completed the Multidimensional Fatigue Inventory (MFI), a visual analogue scale for fatigue (VAS-F) and a Global Perception of Fatigue scale (GPF). Relevant psychometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 51 publications
(70 reference statements)
11
67
0
3
Order By: Relevance
“…The MFI has been widely used for patients with PD. 1,2,11,24 In the present study (N 5 77), the MFI proved to be a reliable intrument to assess fatigue (ICCs 5 0.70-0.87).…”
Section: Measuring Fatiguesupporting
confidence: 48%
See 1 more Smart Citation
“…The MFI has been widely used for patients with PD. 1,2,11,24 In the present study (N 5 77), the MFI proved to be a reliable intrument to assess fatigue (ICCs 5 0.70-0.87).…”
Section: Measuring Fatiguesupporting
confidence: 48%
“…[1][2][3] Prevalence rates reported in the literature range from 32% to 50%. 4,5 Fatigue is often believed to be an independent factor that is negatively associated with activities in patients with PD.…”
Section: Fatigue Is Common In Many Patients With Idiopathicmentioning
confidence: 99%
“…Pavese et al [20] further discuss that due to an effective loss of SERT protein found in their study, SSRI are less likely to be efficacious in PD patients with primary fatigue. A previous observational study by Martinez-Martin et al [43] found a lower prevalence of fatigue in patients treated with amantadine, which is often used to treat fatigue in multiple sclerosis as well. In our study we did not find an association between amantadine intake and any of the fatigue domains in either the primary or secondary fatigue groups.…”
Section: Discussionmentioning
confidence: 94%
“…Total score ranges from 0 and 32 points. The D-FIS questionnaire has been translated into Spanish and adequately validated (29), and has previously been used in celiac disease (30).…”
Section: Assessment Of Fatiguementioning
confidence: 99%